2019
DOI: 10.1177/0956797619887348
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variability in the Association Between Age and Well-Being: The Role of Uncertainty Avoidance

Abstract: Past research has found a mixed relationship between age and subjective well-being. The current research advances the understanding of these findings by incorporating a cultural perspective. We tested whether the relationship between age and well-being is moderated by uncertainty avoidance, a cultural dimension dealing with society’s tolerance for ambiguity. In Study 1 ( N = 64,228), using a multilevel approach with an international database, we found that older age was associated with lower well-being in coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…One explanation for these striking results could be that in both our sample, and the sample included in the Krys et al (2020) study, were composed of university students, whereas the national samples include participants of all ages. Recent research by Lawrie et al (2020) showed a negative relationship between age and life satisfaction in Romania. Therefore, it is possible that younger samples might experience a reference effect such that they are comparing themselves to considerably unhappier older individuals.…”
Section: Discussionmentioning
confidence: 98%
“…One explanation for these striking results could be that in both our sample, and the sample included in the Krys et al (2020) study, were composed of university students, whereas the national samples include participants of all ages. Recent research by Lawrie et al (2020) showed a negative relationship between age and life satisfaction in Romania. Therefore, it is possible that younger samples might experience a reference effect such that they are comparing themselves to considerably unhappier older individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Other cultural dimensions can influence what is perceived as responsive. Socioeconomic status, religiosity, and age differentially affect peoples' priorities regarding autonomy, self-efficacy, and interdependence (e.g., Lawrie et al, 2020;Jiang et al, 2018;Martin et al, 1996;Stephens et al, 2014), and are likely to shape what is perceived as responsive and the impact of different forms of support on health and well-being. These are important topics for future research.…”
Section: Future Directionsmentioning
confidence: 99%
“…A large number of studies have proved that subjective well-being of middle-aged and elderly people is affected by family and individual factors such as age, gender, religious faith, education, marital status, economic status, and self-rated health [ 55 , 56 , 57 , 58 , 59 ]. Some cross-sectional and longitudinal studies have indicated that subjective well-being presents a U-shaped state in the whole life cycle and increases in older age (around age 40–50 years old) [ 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%